An Extremely Rapid Case of Pneumonitis with the Use of Nivolumab for Pancreatic Adenocarcinoma. (1st April 2018) - Costa, Rubens Barros; Benson, Al; Yaghmai, Vahid; Costa, Ricardo L. B.; Zhou, Haijun; Behdad, Amir; Kaplan, Jason B.; Sadim, Maureen; Talamantes, Sarah; Kalyan, Aparna
Abstract : Pancreatic cancer is the fourth most common cancer death in the United States despite comprising a small percentage of the total number of cancer cases. The estimated 5-year overall survival (OS) for patients with distant metastatic disease is approximately 3%. New treatment options are an unmet need and remain an area of active investigation. A 53-year-old male with metastatic pancreatic cancer presented to the hospital with acute-on-chronic respiratory failure approximately 24 hours after receiving a novel therapeutic combination. Chest imaging showed marked changes as concerning for pneumonitis. Infectious workup was negative. The patient had initial clinical improvement after receiving initial intravenous steroids and oxygen support but eventually deteriorated later opting for supportive measures only. With infection ruled out, drug-induced pneumonitis was felt to be the likely cause of the radiologic and clinical changes. The rapidity of onset of symptoms is the aspect being highlighted in this case.